Antifungal Activity of Selaginella plana (Desv. ex Poir.) Hieron Extract Against Candida albicans In Vitro - Warella, Juen Carla; Rahma, Khairunnida; Widodo, Agung Dwi Wahyu; Setiabudi, Rebekah Juniati (Folia Medica Indonesiana, 2023)
Highlights: 1. A study on the medical benefits of Selaginella plana has significant academic value due to its extensive traditional usage among the Moluccan people as a medicinal remedy, especially for its antifungal properties. 2. The findings of this study will allow further screening to determine the mechanism of action of bioactive compounds in inhibiting the growth of Candida albicans Abstract Candidiasis is an opportunistic infection caused by Candida albicans. This infection commonly affects the skin, oral mucosa, vagina, and gastrointestinal tract. Excessive use of azole antifungals in the treatment of Candida albicans infections can lead to the development of resistance. Therefore, it is necessary to explore alternative treatments using medicinal plants such as Selaginella plana, commonly referred to as